Growth and survival of cork oak (Quercus suber) seedlings after simulated partial cotyledon consumption under different soil nutrient contents - Mancilla-Leytón, JuanManuel; Cambrollé, Jesús; Figueroa, ManuelEnrique; Martín Vicente, Ángel (Plant and Soil, 2013)
We examined the importance of partial seed consumption (cotyledon loss) by rabbits in the early establishment of seedlings of cork oaks restricted to nutrient-impoverished soils. To determine the importance of cotyledons in the growth and development of seedlings, we simulated two levels of predation [light (30 % cotyledon loss) and heavy (60 % loss) partial consumption] and two soil nutrient contents (nutrient-poor soil, nutrient-rich soil). Seedlings height, root length, dry root and shoot biomass, specific leaf mass, leaf density, gas exchange, chlorophyll fluorescence parameters and photosynthetic pigment concentrations were determined. Results indicated that effect of nutrient level on the growth of the oak seedlings was more important than that of cotyledon biomass. However, in nutrient-poor soils, cotyledon biomass played a major role in the early performance of cork oaks. Acorns grown in nutrient-rich substrate, despite having greater aerial vigor, were slower to develop a vertical root, and hence less likely to reach permanent moisture. Cotyledon loss caused a decrease in the biomass of roots and shoots when acorns were heavily consumed, and as a result experienced a reduction in net photosynthetic rate, stomatal conductance and chlorophyll concentration. Survival of seedlings was unaffected by either soil type or cotyledon loss. Our results show that effects of soil type on the survival of oak seedlings were more important than those of cotyledon biomass. However, in a competitive situation, cotyledon biomass, as an indicative of growth nutrient support rather than an energy source, could be vital in a nutrient-poor environment, particularly in Mediterranean climate regions and for species with little inherent drought tolerance (as is the case of Quercus spp.), where rapid root growth is required to ensure that contact with soil moisture is maintained over the first summer.
Keywords: acorn; Cotyledon loss; Doñana Natural Park; Nutrient; photosynthesis; Predation; seedling establishment

Why do Corsican Blue Tits Cyanistes caeruleus ogliastrae not use nest boxes for roosting? - Dhondt, André a.; Blondel, Jacques; Perret, Philippe (Journal of Ornithology, 2009)
We compared winter roosting behaviour of Blue Tits Cyanistes caeruleus in the mainland of southern France and on the island of Corsica in small-holed nest boxes. While in southern France Blue Tits use nest boxes for roosting, Corsican Blue Tits do not. We suggest that this behaviour is innate because Corsican wild-caught as well as F1 and F2 birds born in captivity do not use nest boxes in aviaries even when kept adjacent to mainland tits that sleep in boxes. We suggest that the cost/beneﬁt balance differs between mainland France and Corsica: in Corsica, the costs of roosting in the canopy are less than in mainland France because (1) predators, e.g. owls, are rare in Corsica while abundant on the mainland, (2) the permanent evergreen foliage of the dominant tree in Corsica, the holm oak, could be preferred to nest boxes which are not risk-free, and (3) the costs of using cavities for roosting could be higher in Corsica because of increased mammal predator pressure and higher ectoparasite load than on the mainland.
Keywords: á parasitism á; Cyanistes caeruleus ogliastrae; cyanistes caeruleus ogliastrae á; Life-history trait; life-history trait á predation; Parasitism; Predation; Small-holed nest box

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM.; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC.; Blondel, Jacques; Thomas, DonaldW. (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction

Habitat quality as a predictor of spatial variation in blue tit reproductive performance: a multi-plot analysis in a heterogeneous landscape - Lambrechts, MarcelM; Caro, Samuel; Charmantier, Anne; Gross, Nicolas; Galan, Marie-Jo; Perret, Philippe; Cartan-Son, Mireille; Dias, PaulaC; Blondel, Jacques; Thomas, DonaldW (Oecologia, 2004)
Vertebrate studies have rarely investigated the influence of spatial variation in habitat richness on both short-term (breeding) and long-term (offspring recruitment) reproductive performance using simultaneously multi-patch, multi-habitat type and multi-year approaches at landscape level. Here we present results of such an approach using the influence of two oak tree (Quercus ilex, Q. humilis) species on reproductive performance in Corsican blue tits (Parus caeruleus ogliastrae) as a model system. We found that blue tits breeding in rich broadleaved deciduous patches consistently laid eggs earlier in the season, and produced larger clutches and more fledglings of higher quality, than those breeding in poor evergreen patches. Also, parents, especially males, were in better physical condition in the broad-leaved deciduous than in the evergreen patches. Surprisingly, estimates of long-term effects of reproduction, such as recruitment rates of locally born offspring, did not differ between the two habitat types. Our results suggest that short-term breeding performance and phenotypic quality of both chicks and parents do not necessarily provide reliable information about contributions to following generations at a scale larger than that of the local study plot. Differences in reproductive performance between the two oak habitat types could not be attributed to densitydependent effects, differences in levels of nest predation, or differences in age structure of the birds. We suggest that habitats that are optimal for breeding are not necessarily optimal for survival after the breeding season.
The following values have no corresponding Zotero field: publisher: Springer-Verlag
Keywords: Habitat quality; Parus caeruleus; Predation; Quercus; reproduction

Acorn predation and seedling production in a low-density population of cork oak (Quercus suber L.) - Herrera, Javier (Forest Ecology and Management, 1995)
Prospects for cork oak recruitment were examined in a scrub-dominated area with low tree density in southern Spain by sowing acorns experimentally in a variety of sites. Seeds placed on the ground surface were invariably eaten within a few months by a variety of vertebrate herbivores (cattle, red deer, fallow deer, wild boar and rabbits). Predation reached 100% whether acorns were placed beneath trees or more than 100 m away from trees. Seeds placed under dense heath scrub were also rapidly removed, although their final fates could not be ascertained. Single acorns buried under open or dense scrub experienced the lowest predation (52% and 0%, respectively) and had relatively high emergence rates (38% and 60%, respectively). Heavy shoot browsing occurred in both scrub types, and out of the 49 buried acorns which produced a shoot, only two seedlings were alive 1 year after germination. None survived 2 years after sowing.
Keywords: herbivory; Predation; Quercus suber; seedling production